Outbreak and host range of Ceratocystis fimbriata ITS5 causing a lethal wilt disease on Lansium domesticum in South Sumatra, Indonesia - RIKO FIRMANTO; AHMAD MUSLIM; SUWANDI SUWANDI; CHANDRA IRSAN; HARMAN HAMIDSON; RAHMAT PRATAMA; YOSSI APRIAN NURSALIM (Society for Indonesian Biodiversity, 2026)
Abstract. Firmanto R, Muslim A, Suwandi, Irsan C, Hamidson H, Pratama R, Nursalim YA. 2026. Outbreak and host range of Ceratocystis fimbriata ITS5 causing a lethal wilt disease on Lansium domesticum in South Sumatra, Indonesia. Biodiversitas 27 (4): d270424. https://doi.org/10.13057/biodiv/d270424. Lethal wilt disease, first reported on Duku (Lansium domesticum) in 2014, has rapidly expanded from Ogan Komering Ulu to multiple regencies across South Sumatra. By 2021, the epidemic reached Muara Enim, transitioning into an increasingly severe outbreak that threatens local biodiversity. This study aims to evaluate current disease development and severity in Muara Enim and characterize the genetic variation and host range of the associated pathogen. Between 2023 and 2025, we surveyed 24 L. domesticum orchards, using plots purposively positioned in high-incidence zones to document the epidemic's maximum virulence. Identification of eight fungal isolates from infected sapwood was performed via morphological observation and multi-gene phylogenetic analysis using Internal Transcribed Spacer (ITS) and -tubulin markers. Pathogenicity was confirmed by Koch’s postulates and host-range testing across diverse plant species. Molecular analysis of these representative isolates confirmed their identity as the ITS5 haplotype of Ceratocystis fimbriata, suggesting this haplotype is a key driver of the current outbreak. Results indicated high disease virulence; while regional averages varied, disease incidence reached 100% in the most severely affected orchards (e.g., Ujan Mas Lama) by June 2025. In pathogenicity trials, isolates exhibited aggressive infection patterns, producing significant lesions across all tested hosts; Parkia speciosa and Persea americana were identified as particularly vulnerable. These results indicate that C. fimbriata represents a serious threat to L. domesticum orchards and may endanger the long-term persistence of local populations in South Sumatra. To mitigate this impact, urgent management strategies are required, including the immediate removal and destruction of infected trees (sanitation felling), strict pruning hygiene to prevent wound-mediated infection, and careful selection of non-host species in mixed-planting systems.